Spherical symmetry and nonmagnetic dielectrics in analog models of gravity - Bittencourt, Eduardo; Klippert, Renato; Silva, Diego Renan da [UNESP]; Goulart, Erico (Amer Physical Soc, 2021)
Nonmagnetic and spherically symmetric dielectric material media are investigated in their generality as analog models, in the domains of geometrical optics, for a few relevant static and spherically symmetric solutions of gravitation, including black holes and wormholes. Typical and desirable gravitational features are systematically linked to the nonlinear properties of the phenomenological dielectric permittivity of the medium. From this, the limitations of such analogies are explored in terms of their corresponding geometric flexibility, dielectric configurations, and causal structure.